2017
DOI: 10.22452/mjes.vol54no1.3
|View full text |Cite
|
Sign up to set email alerts
|

Currency Crises and Purchasing Power Parity in the Asian Countries: Evidence Based on Second-Generation Panel Unit-Root Tests

Abstract: This study applies a second-generation panel unit-root tests to determine the stochastic properties of real exchange rates for 14 Asian countries. Based on three popular alternative definitions of a currency crisis, we identify the several important currency crisis episodes in the region. The purchasing power parity (PPP) hypothesis was overwhelmingly supported after accommodating these heterogeneous noisy and unstable observations. Our panel unit-root test that controls for cross-sectional dependence and is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…These results are also consistent with Ha (2018). Using panel data methods and considering structural breaks, Ha (2018) found that the PPP hypothesis is valid in nine Southeast Asian countries, namely Vietnam, Laos, Cambodia, Thailand, Myanmar, Malaysia, Singapore, Indonesia, and the Philippines between July 1997and August 2008. Soon et al (2017, using second-generation panel unit root tests, also found evidence for the PPP hypothesis in Southeast Asian countries.…”
Section: Panel Cointegrationmentioning
confidence: 99%
“…These results are also consistent with Ha (2018). Using panel data methods and considering structural breaks, Ha (2018) found that the PPP hypothesis is valid in nine Southeast Asian countries, namely Vietnam, Laos, Cambodia, Thailand, Myanmar, Malaysia, Singapore, Indonesia, and the Philippines between July 1997and August 2008. Soon et al (2017, using second-generation panel unit root tests, also found evidence for the PPP hypothesis in Southeast Asian countries.…”
Section: Panel Cointegrationmentioning
confidence: 99%